Allometric Models to Estimate Carbon Content in Arecaceae Based on Seven Species of Neotropical Palms - Avalos, Gerardo; Cambronero, Milena; Alvarez-Vergnani, Carolina (Frontiers in Forests and Global Change, 2022)
21We present allometric models for estimating total carbon content and above ground carbon (AGC) for the Arecaceae family, and for 7 abundant neotropical palm species (the canopy species Socratea exorrhiza (n = 10) and Iriartea deltoidea (n = 10), the sub-canopy palm Euterpe precatoria (n = 10), and the understory species Asterogyne martiana (n = 15), Prestoea decurrens (n = 10), Geonoma interrupta (n = 10) and Chamaedorea tepejilote (n = 22). Understanding the allometry of functional groups such as palms is critical for improving carbon stocks estimates in tropical forests and determining how allometric differences affect species functional diversity. The research was carried out in the tropical rainforests of the Caribbean slope of Costa Rica. We harvested 87 palms of a wide range of sizes, and separated them into roots, stems, and leaves, measured their fresh and dry biomass, and calculated their carbon content, tissue density, and dry mass fraction (dmf). Our general palm model estimating total carbon content based on these 7 species and 87 samples accounted for 92% of the variation across species. We generated a similar model to estimate AGC and explained 91% of the variation. We compared our AGC model with two models used to estimate palm carbon content: Goodman et al. (2013)´s and Chave et al. (2014)´s models and found that all three converged on the estimation of AGC although our model was the most parsimonious because it achieved the same efficiency with only two variables, stem diameter and stem height. To improve the accuracy of allometric models we need to incorporate more species, a greater diversity of growth forms, a wider range of sizes, a larger sample size, and more diversity of habitats dominated by palms. Estimating carbon content using allometric approaches could benefit from more consistency in data collection across plant groups.